2009
DOI: 10.1007/s12017-009-8110-1
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine Potentiates Seizures and Cell Loss Induced by Pilocarpine Treatment

Abstract: Patients affected by recurrent seizures frequently present increased homocysteine plasma levels in consequence of treatment with antiepileptic drugs. Homocysteine is proconvulsant and can affect the response to antiepileptic drugs. In addition, high homocysteine plasma levels represent a risk factor for cardiovascular and neurodegenerative diseases. To better define the role of increased homocysteine in epilepsy, we analyzed the effects of homocysteine pretreatment in the pilocarpine model of status epilepticu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 52 publications
(78 reference statements)
1
20
0
Order By: Relevance
“…In agreement with this finding it was suggested that systemic administration of Hcy at high doses provokes convulsive attacks in mice and it was proposed that similar detrimental effects can be manifested in patients suffering from temporal lobe epilepsy (Baldelli et al, 2010). Consequently, the Hcy-derived chemical reactive metabolites are thought to have an important role in Hcy-induced seizures.…”
Section: Toxicity Of Homocysteine To Neural Cells As a Stroke Risk Fasupporting
confidence: 56%
“…In agreement with this finding it was suggested that systemic administration of Hcy at high doses provokes convulsive attacks in mice and it was proposed that similar detrimental effects can be manifested in patients suffering from temporal lobe epilepsy (Baldelli et al, 2010). Consequently, the Hcy-derived chemical reactive metabolites are thought to have an important role in Hcy-induced seizures.…”
Section: Toxicity Of Homocysteine To Neural Cells As a Stroke Risk Fasupporting
confidence: 56%
“…Intriguingly, increased Adk expression is frequently observed in chronic epileptic tissue, accounting for continuous removal of adenosine and shifting chemical equilibrium toward AMP synthesis (Boison, 2008). Disturbances in folate metabolism (e.g., low‐folate diet or MTHFR mutations/reduced enzymatic activity) have been associated with increased CSF levels in homocysteine, a proconvulsant, and seizures (Goyette et al., 1995; Ono et al., 2000; Chen et al., 2001; Baldelli et al., 2010). AMP, adenosine monophosphate; ADK, adenosine kinase; DNMTs, DNA methyltransferases; MAT, methionine adenosyltransferase; MTHFR, methylene tetrahydrofolate reductase; 5‐MTHF, 5′ methylene tetrahydrofolate; SAHH, S‐adenosylhomocysteine hydrolase; THF, tetrahydrofolate.…”
Section: Transmethylation Metabolism and Diseasementioning
confidence: 99%
“…Of interest, there is a considerable phenotypic overlap of severe MTHFR deficiency with Angelman syndrome and Rett syndrome, both of which are autism spectrum disorders with high incidence of seizures. Furthermore, the 677C>T MTHFR variant, which causes mild reduction in MTHFR activity, is a genetic risk factor for seizures or epilepsy (Ono et al., 2000; Baldelli et al., 2010). Cerebral folate deficiency (CFD) syndrome is a pediatric neurologic disorder characterized by low cerebrospinal fluid (CSF) levels of 5‐MTHF.…”
Section: Transmethylation Metabolism and Diseasementioning
confidence: 99%
“…Further, some studies have demonstrated that hyperhomcysteinemia might be involved in the pathophysiology of many neuropsychiatric disorders, including brain atrophy, epilepsy, and Alzheimer's disease [15][16][17][18]. But homocysteinemia-lowering therapies from an early age are it effective at preventing neuropsychiatric disorders?…”
Section: Discussionmentioning
confidence: 99%